Legal Due To Cancellation Of Deed Bonding The Land Buying - Sukardi, Alek; Darwati, Darwati (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The importance of land for human life, because human life can not be separated from the ground. Land issues can lead to disputes, among others, stemming from the binding sale and purchase of land. The binding agreement for the sale and purchase of land, in everyday practice, is carried out by the community at the notary's office. This agreement is an agreement that precedes the sale and purchase agreement of the land, which must be made before the Land Deed Maker Official. The problem; 1. How is the implementation of the binding sale and purchase of land according to Law Number 5 of 1960 concerning the Basic Agrarian Law? 2. What are the legal consequences of the cancellation of the binding deed of sale and purchase of land. The discussion is carried out through a normative research study.The binding is intended as a preliminary agreement from the main intention of the parties to transfer land rights. This sale and purchase agreement contains promises to buy and sell land if the requirements needed for it have been met, and is a form of agreement that arises from legal needs that develop in society. The binding sale and purchase of land is an anonymous agreement, because it is not found in the forms of agreements regulated in the Civil Code. The binding agreement for the sale and purchase of land is an implementation of the principle of freedom of contract, where the parties can freely determine their will. The binding sale and purchase is a form of agreement that arises from the legal needs that develop in society. An agreement can not always run according to the agreement desired by the parties, including the binding agreement for the sale and purchase of land which can be canceled by the parties or even by one of the parties, or also canceled by the court. For these legal actions, there will be legal consequences that must be obeyed by the parties.